Critical Illness Polyneuropathy and Functional Outcome in Subjects with Covid-19: Report on Four Patients and a Scoping Review of the Literature - Domenico Intiso; Antonello Marco Centra; Antonio Giordano; Andrea Santamato; Luigi Amoruso; Filomena Di Rienzo (Medical Journals Sweden, 2022)
Patients with COVID-19 may develop a range of neurological disorders. We report here 4 COVID-19 subjects with intensive care unit-acquired weakness and their functional outcome. In addition, a scoping review of COVID-19 literature was performed to investigate this issue. Of the post-COVID-19 patients admitted to our Neuro-Rehabilitation Unit, 4 (3 males, 1 female; mean age 59.2 ± 8.62 years) had intensive care unit-acquired weakness, diagnosed with electromyography. Muscle strength and functional evaluation were performed on all patients with Medical Research Council, Disability Rating Scale and Functional Independence Measure, respectively, at admission, discharge and 6-month follow-up after discharge. Electromyography revealed that 3 subjects had critical illness polyneuropathy and 1 had critical illness polyneuropathy/critical illness myopathy. At follow-up, the 3 subjects with critical illness polyneuropathy reached full recovery. The patient with critical illness polyneuropathy/critical illness myopathy showed moderate disability requiring bilateral ankle foot-orthosis and support for ambulation. The scoping review retrieved 11 studies of COVID-19 patients with intensive care unit-acquired weakness, concerning a total of 80 patients: 23 with critical illness myopathy (7 probable), 21 with critical illness polyneuropathy (8 possible), 15 with critical illness polyneuropathy and myopathy (CIPNM) and 21 with intensive care unit-acquired weakness. Of 35 patients who survived, only 3 (8.5%) reached full recovery. All 3 had critical illness myopathy, but 2 of these had a diagnosis of probable critical illness myopathy. Intensive care unit-acquired weakness commonly occurred in subjects with COVID-19. Recovery was variable and a low percentage reached full recovery. However, the heterogeneity of studies did not allow definitive conclusions to be drawn. LAY ABSTRACT Patients with COVID-19 may develop a range of neurological disorders. We report here 4 cases of COVID-19 patients with intensive care unit-acquired weakness and their functional outcome. In addition, a scoping review of the COVID-19 literature was performed to investigate the occurrence of, and recovery from, intensive care unit-acquired weakness and sub-types (critical illness polyneuropathy, critical illness myopathy and critical illness polyneuropathy/critical illness myopathy) in subjects with COVID-19. Of these 4 patients, the 3 patients with critical illness polyneuropathy reached full recovery. The patient with critical illness polyneuropathy/critical illness myopathy showed moderate disability, requiring use of a bilateral device (ankle foot-orthosis). The scoping review of studies of COVID-19 patients with intensive care unit-acquired weakness retrieved a total of 80 patients: 21 with intensive care unit-acquired weakness, 23 with critical illness myopathy, 21 with critical illness polyneuropathy, and 15 with critical illness polyneuropathy/critical illness myopathy. Intensive care unit-acquired weakness commonly occurred in COVID-19 subjects, but the outcome was variable and a low percentage reached full recovery. COVID-19 subjects can develop long-term consequences and limitations, particularly those with intensive care unit-acquired weakness, who need more rehabilitation. New rehabilitative strategies and well-designed studies investigating the benefit of rehabilitation are necessary.